Playing with the Text; stimulation of deep reading comprehension and critical thinking: a methodological challenge - Arrieta Molina, Gina (2016)
This paper discusses the difficulties presented in deep reading comprehension in college primer income; during the Humanistic Studies. This phenomenon is analyzed in relation to the lack of methodological strategies that encourage teachers constructively reading practice aiming to develop critical thinking in learners. Making the unreview of other university contexts, they detect achieved some important aspects such as functional illiteracy and low levels of skill in reading of the learners. In response to previous behold reference to the implementation of a teaching strategy executed students primer income Integrated Course Humanities Campus of Paradise (Headquarters Atlantic UCR), whose essential fin root in Foster playfulness is done to recreate some texts suggested by teachers and ensure reading comprehension deep and the development of critical thinking.